Gearing up for optical microrobotics: micromanipulation and actuation of synthetic microstructures by optical forces. Issue 4 (7th January 2013) - Palima, Darwin; Glückstad, Jesper
<x xml:space="preserve">Abstract</x> Optics is usually integrated into robotics as part of intelligent vision systems. At the microscale, however, optical forces can cause significant acceleration and so optical trapping and optical manipulation can enable the noncontact actuation of microcomponents. Microbeads are ubiquitous optically actuated structures, from Ashkin's pioneering experiments with polystyrene beads to contemporary functionalized beads for biophotonics. However, micro‐ and nanofabrication technologies are yielding a host of novel synthetic structures that promise alternative functionalities and new exciting applications. Recent works on the actuation of synthetic microstructures using optical trapping and optical manipulation are examined in this review. Extending the optical actuation down to the nanoscale is also presented, which can involve either direct manipulation of nanostructures or structure‐mediated approaches where the nanostructures form part of larger structures that are suitable for interfacing with diffraction‐limited optical fields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>